Faktor yang mempengaruhi kepatuhan kemoterapi pada pasien kanker payudara: Literature review - Nurfadhilah, Naila; Revalina, Regita Ayu; Choironissa, Nazwa Shifa; Salma, Nisrina Nabila; Nursifa, Anis Fauziah; Faulina, Allyssa Rizky; Firdaus, Muhammad Aghna; Ridwan, Heri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Breast cancer is the most common cancer in women worldwide, and chemotherapy is one of the primary methods of treatment. However, the severe side effects of cytotoxic drugs often lead to poor patient adherence, which directly impacts the likelihood of recurrence and mortality. Purpose: To collect and analyze the latest scientific evidence from 2020 to 2025 to identify key factors influencing chemotherapy adherence in women with breast cancer. Method: This study employed a literature review design following the PRISMA guidelines. Articles were searched through Google Scholar, Semantic Scholar, and PubMed databases using the keywords